A Proposed Methodology for Integrated Architectural Design of Smart Hospitals - Helmy Elhefnawy, Mohamed (EAI Endorsed Transactions on Smart Cities, 2020)
INTRODUCTION: Urgent need has recently emerged to transform hospitals from buildings that not only achieve functional requirements, but also comply with modern technologies. This is so that they are able to self-adapt to external conditions and change their behavior according to users. This is compatible with emerging trends to convert cities and buildings in developing countries to smart. OBJECTIVES: To develop a comprehensive methodology for proper dealing with smart materials & systems when constructing and finishing hospitals, leading to defining principles of an integrated architectural design for smart hospitals. METHODS: The descriptive analytical approach included theoretical background on concept of smart hospitals, types of smart materials & systems and their role in hospital design. RESULTS: An integrated methodology for proper architectural dealing with hospitals to allow them to be smart, which the study recommends to follow and complement between smart materials and systems. CONCLUSION: The research conceived a proposed methodology for the architectural design of smart hospitals and identified mechanisms for utilizing smart materials and systems in developing hospital designs.